Warunki wdrożenia rachunku kosztów działań na potrzeby controllingu w oddziałach rejonowych Poczty Polskiej - Czubakowska, Ksenia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The implementation of Activity Based Costing in postal in Poland is a multistage process which has been realized since 2003. The article presents a general concept of the implementation of Activity Based Costing, discusses Activity Based Costing and shows problems which may appear while its implementation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 64-71